PTH-028 Real world surveillance of barrett's oesophagus – does it make a difference using the prague classification or following seattle biopsy protocol?. (22nd June 2015) - Ghuman, S; Asghar, K; Evans, J; Kakhi, S; Hawkes, N
Abstract : Introduction: BSG Barrett's Surveillance guidance recommends that the Prague Classification (PC) should be used to describe a Barrett's segment and Seattle Protocol (SP) be used when taking biopsies. Previous studies have reported poor compliance with such protocols. We sought to investigate the extent to which adherence to advice affected outcomes in our patient cohort. We aimed to investigate the impact of 1) reported use of the Prague classification and 2) adherence to the Seattle protocol, on the detection of all dysplasia and advanced dysplasia (HGD, or in-situ adenocarcinoma). Method: HICCS Endoscopic Reporting System was searched for all detected Barrett's oesophagus between Oct 2010–Oct 2014 (n = 587 procedures). Only specific surveillance cases were included (index and specific recall cases excluded). Endoscopy reports were checked and histology results retrieved from the Welsh Clinical Portal system. Differences in dysplasia detection rates for 1) PC used versus PC not used, and 2) SP followed versus SP not followed were tested using the Chi-squared test. Numbers of biopsies in each SP group were compared using two-tailed t-test. Significance level set at p < 0.05. Results: In the 4 year study period, 367 Barrett's surveillance procedures were performed in 220 patients. PC was reported in 106 (28.9%) and SP followed in 116 (31.6%) of procedures. The dysplasia rates are shown in the Table. There was a significant increase in detection rate of all types of dysplasia and advanced dysplasia (AD) when PC was used and where SP was followed. Significantly more biopsies were taken in the SP followed group, both for short (p = 0.037) and longer (>3 cm) segments (p < 0.00001). Conclusion: Adherence to recommended reporting and biopsy protocols may just reflect deeper interest in Barrett's surveillance or greater experience level. Even if only surrogate markers for 'quality' of examination, their use marked clinically relevant differences in dysplasia detection, which in turn is linked to numbers of patients who may require endotherapy or radiofrequency ablation. Disclosure of interest: None Declared.